Construire la mémoire collective de l’Indépendance : les manuels d’histoire au Guatemala à la fin du XIXe siècle - Emilie Mendonça (Les Cahiers ALHIM)
The history of Central America, too often drowned in a global history of Latin America, has many singularities- such as the Independence, which was conquered not by the weapons of a popular upheavals but with a piece of paper covered in ink. Moreover, the Independence of Guatemala in 1821 was soon threatened by the annexation of Central America to the Mexican Empire of Iturbide, before a Federation of United Provinces was created, whose life was short but eventful. This birth raises many questions: how can one define a founding and unifying event in which the people had not taken part? How can one pass on its memory? Such are the questions guiding this study of the Independence as it is told in the late 19th century Liberal Guatemala history schoolbooks- at the time when the national history was shaped by Marure and Montufar and the compulsory, public school was founded, making the building of a common past possible.